Upconversion-based nanosystems for fluorescence sensing of pH and H2O2. Issue 9 (23rd March 2021) - Sun, Chunning; Gradzielski, Michael
Abstract : Non-contact and conventional upconversion-based nanosystems were designed for the fluorescence sensing of pH and H2 O2 . Abstract : Hydrogen peroxide (H2 O2 ), a key reactive oxygen species, plays an important role in living organisms, industrial and environmental fields. Here, a non-contact upconversion nanosystem based on the excitation energy attenuation (EEA) effect and a conventional upconversion nanosystem based on the joint effect of EEA and fluorescence resonance energy transfer (FRET) are designed for the fluorescence sensing of H2 O2 . We show that the upconversion luminescence (UCL) is quenched by MoO3− x nanosheets (NSs) in both systems due to the strong absorbance of MoO3− x NSs in the visible and near-infrared regions. The recovery in UCL emissions upon addition of H2 O2 enables quantitative monitoring of H2 O2 . Benefiting from the non-contact method, hydrophobic OA-NaYF4 :Yb, Er can be used as the luminophore directly and ultrahigh quenching efficiency (99.8%) is obtained. Moreover, the non-contact method exhibits high sensitivity toward H2 O2 with a detection limit of 0.63 μM, which is lower than that determined by simple spectrophotometry (0.75 μM) and conventional upconversion-based nanocomposites (9.61 μM). As an added benefit, the same strategy can be applied to the sensing of pH, showing a broad pH-responsive property over a range of 2.6 to 8.2. The successful preparation of different upconversion-based nanosystems for H2 O2 sensing using the same material as the quencher provides a new design strategy for fluorescence sensing of other analytes.